THE ISLAMIC PERSPECTIVE OF CHANGES IN GOVERNMENT ADMINISTRATION AND LAW: With Special Reference to the Development of Legal Political System in Post-Reformasi Indonesia (JOURNAL OF INDONESIAN ISLAM, 2012)
The debate surrounding theocracy and secularism among Indonesian Muslims has been recorded since pre-independence period in early part of the 20th Century until now. This article is an effort to examine the compatibility of Islam with the idea of democracy and the inclusion of shari’ah in it. The focus is on government administration and law. Using the approach of Islamic law perspective, the writer argues that the dichotomy between theocracy and secularism does not apply to Indonesia because he treats shari’ah as merely a philosophical reference. Shari’ah evolves as a living organism that transcends any debatable issues for benefit of ummah. In contemporary Indonesian political context, the substance of shari’ah had been manifested by implementing a democratic system based on a legal foundation for the benefit and welfare of ummah. Therefore, some political-legal institutions like Constitutional Court and Anti-Corruption Commission are considered as part of shari’ah implementation although they are not textually sanctioned by shari’ah.